Influence of Environment on Learning Improvement and Student Characters Strengthening in Covid-19 Pandemic - Uci Dwi Cahya; Farahdiba Thahura; Meylia Sari (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2021)
As a result of the Covid-19 pandemic, it has greatly impacted the world, especially in the field of education, therefore, with increasingly developing technological capabilities, the teaching and learning process in schools is also carried out online. This study aims to analyze the character values ​​of students, as well as describe the design of student character learning in accordance with Pancasila as the basis of the State, and students are able to instill character values ​​in everyday life. This research was conducted at MI TerpaduTahfidz Al Mubarak Langsa in grades 3 and 4 with 20 students per class, and 4th grade teachers. The data analysis method used is a qualitative method by applying field research, namely by field observations, by observing each object which is done online through a video call application. From the results of the analysis, it was known that the character of students in grades III and IV of Integrated MI Tahfidz Al Mubarak 80% is very in accordance with the values ​​of Pancasila because the learning system is carried out always under the supervision of parents and teachers with a maximum number of ten students in one online class. In one class there are two teachers who teach in each class, every day parents must send reports on student progress to their respective class teachers. This is also inseparable from the role of parents in educating their children at home even though the state of the teaching and learning process is carried out online.